Modification of kaolinite clay using benzyltriethylammonium chloride as a surfactant: Preparation and characterization - Meftah Elgubbi, Hana; Salhah Othman, Siti; Wahida Harun, Farah (International Journal of Engineering and Technology, 2020)
Natural kaolinite clay from Perak, Malaysia with cation exchange capacity (CEC) of 2.5 meq/100g was modified using cationic surfactant, benzyltriethylammonium chloride (BTEA-Cl), at 0.5, 1.0, 1.5 and 2.0 times the CEC. A number of techniques, namely energy dispersive X-ray (EDX) spectroscopy, X-ray diffraction (XRD), Fourier-transform infrared (FTIR) spectroscopy, scanning electron microscopy (SEM), and Brunauer-Emmett-Teller (BET) nitrogen adsorption-desorption were then used for characterization of the kaolinite and/or organo-modified kaolinite clays. The presence of alkyl groups as a result of successful intercalation of cationic surfactant within the organo-kaolinite layers of the clay was exhibited by the FTIR spectra. The SEM microphotographs exhibited good dispersion of the natural clay particles and slight agglomeration in the organo-modified clay particles. XRD patterns showed that the d001 spacing of the natural kaolinite clay increased from 7.12 Å to between 7.20 - 7.34 Å for the organo-modified clays. Following the BET nitrogen adsorption-desorption technique, all clay samples were of Type IV with narrow hysteresis loops. Surface areas of the clays showed drastic decrease from (25.34 m2/g) for natural kaolinite clay to between 5.90 - 13.11 m2/g for organo-modified clays. The results suggested that modification of natural kaolinite clay using cation surfactant had successfully occurred. The modification can therefore be further applied for alteration and improvement of the properties of natural clays for various industrial applications.
Keywords: Kaolinite; Cation Exchange Capacity; Benzyltriethylammonium Chloride; Organo-Modification; Characterization.